2004
DOI: 10.1111/j.1439-0310.2004.00995.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Previous Experience Over Control of Access to Food and Light on the Level of Frustration‐Induced Aggression in the Domestic Hen

Abstract: Animals have been shown to respond to frustration with increased aggression and activity. Aversive environmental conditions are also known to affect reaction to frustrating events. One pertinent and aversive environmental factor that has been shown to affect aggression is exposure to uncontrollable rewards and punishments. Although used largely in experimental contexts, this situation is similar to that found in modern intensive farming systems, where environmental and social conditions are largely controlled.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…For end-of-lay hens, there is little scientific evidence regarding when hens experience negative affective states and craving for water. Haskell et al (2004), using water deprivation in an operant conditioning test, showed that 2 h of water deprivation induced redirected aggression towards a subordinate hen. Similar aggressive behaviours have been demonstrated in laying hens deprived of water for 6 h (Forkman et al, 2000) as well as pacing, excessive preening or redirected pecking in earlier work by Duncan and Wood-Gush (1972) of feed or water-deprived hens.…”
Section: Preventive Measuresmentioning
confidence: 99%
“…For end-of-lay hens, there is little scientific evidence regarding when hens experience negative affective states and craving for water. Haskell et al (2004), using water deprivation in an operant conditioning test, showed that 2 h of water deprivation induced redirected aggression towards a subordinate hen. Similar aggressive behaviours have been demonstrated in laying hens deprived of water for 6 h (Forkman et al, 2000) as well as pacing, excessive preening or redirected pecking in earlier work by Duncan and Wood-Gush (1972) of feed or water-deprived hens.…”
Section: Preventive Measuresmentioning
confidence: 99%
“…As an indicator of drinking motivation, compensatory drinking has been shown to increase proportionally with the duration of water deprivation from 6 to 24 h in broiler chickens ( Sprenger et al, 2009 ; Vanderhasselt et al, 2014 ). In an operant conditioning test, Haskell et al (2000 , 2004 ) found that water deprivation of periods of 2 and 6 h caused laying hens to display redirected aggression toward a subordinate individual when access to water in a dish was thwarted using a clear lid. Other behavioral changes, such as increased drinking duration (after 24–32 h of water deprivation), increased proximity to the drinkers (after 18 h of deprivation), and reduced standing (after 18 h of deprivation) have been observed in connection to water deprivation when periods of 0, 12, 18, 24, and 32 h were assessed ( Rault et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The point in which birds begin to experience negative emotional states in relation to the extent of water deprivation is unclear, though the few existing motivation testing and behavioral studies may offer some suggestions. After as little as 2 h of water deprivation, increased levels of redirected aggression within a test arena have been noticed in laying hens ( Haskell et al, 2004 ), which may suggest that birds begin to experience negative emotional states around this time. Compensatory water consumption in broilers was observed on farm after 6 h of water deprivation.…”
Section: Discussionmentioning
confidence: 99%
“… 65 On the other hand, the intensity of aggression toward conspecifics can be attributed to “frustration” and “redirection,” critical signs of societies with low social tolerance. 57 , 66 The aggression-based copers retained higher average facial temperatures after an initial 10-min of predator exposure than their nonaggression-based counterparts, thus, possibly lower emotional arousal; it might indicate their predisposed neural underpinnings, which made them “proactive,” 67 i.e., better equipped to engage and cope with stressful situations. In other words, the aggression-based copers were more efficient in controlling (albeit not voluntarily) emotional arousal than nonaggression-based copers with regard to the activities of the autonomic sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%